State-owned enterprises also face up to corporate scandals: a systematic literature review in the 21st century - Lopes, Carlos F. (2024)
This review sheds light on corporate scandals in State-Owned Enterprises (SOEs) from 2000 to 2022. Our objectives include highlighting the importance of studying SOE scandals, examining their relationship with SOEs, identifying the unique characteristics of SOEs compared to non-SOE publicly traded companies, summarizing existing literature, and identifying areas for future research. Theoretical exploration of SOEs reveals insights into governance structures, financial practices, and the delicate balance between state control and commercial imperatives. This study uses a systematic literature review methodology to synthesize and evaluate relevant studies. Scopus and Web of Science databases were used, and they provide a comprehensive view. This study covers SOEs, financing, cash flow manipulation, political ties, market credibility, intra-industry spillovers, and corruption-related scandals. The study highlights the importance of ongoing scrutiny to gain insight into governance mechanisms, auditing, contracting practices, and market-oriented incentives in SOEs. It also identifies critical gaps, emphasizing the need for up-to-date research to inform effective governance practices. The authors identified trends and gaps, highlighting the impact of political ties and scandals. The study provides theoretical insights and practical implications for practitioners and policymakers.